Improving discharge planning using the re‐engineered discharge programme. (18th October 2018) - Roberts, Sterling; Moore, Leslie C.; Jack, Brian
Abstract: Aims: (a) Assess nurses' readiness to learn (RTL) before receiving education on the re‐engineered discharge (RED) programme and (b) measure utilization of the RED discharge process from patient chart reviews following an educational intervention. Background: Preventable readmissions are of great concern. Rural areas are at a disadvantage, due to decreased access to health care and other disparities. Methods: Sixty‐nine participants completed the Self‐Directed Learning Readiness Scale prior to the RED education intervention. Thirty‐minute education interventions were provided addressing various learning preferences. Results: Participants scored high M  = 219.8 ( SD 23.7) on the SDLR, indicating nurses' high RTL prior to educational intervention. Chart reviews found usage of the RED 12 actionable item pre‐intervention, ( n  = 60) M  = 6.55 ( SD 1.478) compared to post‐intervention ( n  = 60) M  = 10.08 ( SD 1.544) indicated statistically significant improvement in pre‐discharge patient education and planning ( t =  17.730, p  = 0.000 [CI 3.13–3.93]). Conclusion: Current study found that nurses with higher levels of RTL who underwent RED educational sessions significantly improved delivery of the RED process documented in the medical record. Implications for nursing management: Those responsible for education initiatives must make understanding nurses' learning preferences a priority to improve the quality of bedside practice.